TINDAK TUTUR EKSPRESIF GURU DALAM PEMBELAJARAN BAHASA INDONESIA DI KELAS X MAN 1 SIJUNJUNG - Widya Putri; Tressyalina; Ermawati Arief; Herlin Triana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the forms of teachers’ expressive speech acts and the politeness strategies used in Indonesian language learning at Grade X of MAN 1 Sijunjung. This qualitative study employed a descriptive method, with data collected through the Simak Libat Cakap (SLC) technique. The findings reveal eight forms of expressive speech acts: praising, criticizing, congratulating, blaming, thanking, complaining, insinuating, and apologizing. In addition, four politeness strategies were identified: bald-on-record, positive politeness, negative politeness, and off-record. The findings indicate that the appropriate use of expressive speech acts and politeness strategies supports effective classroom interaction and strengthens teacher–student relationships in the learning process.